DAA‐based antiviral treatment of patients with chronic hepatitis C in the pre‐ and postkidney transplantation setting. (7th July 2016) - Beinhardt, Sandra; Al Zoairy, Ramona; Ferenci, Peter; Kozbial, Karin; Freissmuth, Clarissa; Stern, Rafael; Stättermayer, Albert Friedrich; Stauber, Rudolf; Strasser, Michael; Zoller, Heinz; Watschinger, Bruno; Schmidt, Alice; et al.
Summary: DAA‐based regimens for chronic hepatitis C infection encourage treatment of "difficult‐to‐treat" cohorts. This study investigated efficacy and safety of DAA‐based regimens in HCV patients on dialysis or postkidney or liver/kidney transplantation. Twenty‐five patients treated with DAA combinations were evaluated: 10 were on dialysis (eight: hemodialysis, two: peritoneal dialysis), eight were kidney transplant recipients, and seven were liver/kidney transplant recipients. Except for one patient treated with daclatasvir ([DCV]/60 mg/QD)/simeprevir ([SMV]/150 mg/QD), the others received sofosbuvir‐based regimens ([SOF];400 mg/QD) combined with SMV:eight, DCV:13 or either ledipasvir ([LDV]90 mg/QD), ribavirin ([RBV];weight based) or pegylated interferon/RBV. HCV‐RNA was determined by Abbott RealTime (LLOQ]:12 IU/ml) or Roche AmpliPrep/COBAS TaqMan assay (LLOQ:15 IU/ml); treatment response evaluated every 4 weeks, at the end of treatment, and 4 and 12 weeks thereafter. Twenty‐four (96%) patients achieved SVR 12/24 (ITT‐analysis). Mean treatment duration was 15.1 ± 5.1 weeks (±SD), and two patients terminated prematurely – both reached SVR12. Six patients were hospitalized due to complications of underlying disease. One patient achieved SVR24 but was re‐infected (week 27). Kidney function remained stable; serum creatinine increased in only one patient – SOF was reduced to 400 mg/48 h. Treatment with DAA combinations in renally impaired HCV patients is highly effective and well tolerated. These findings call for further controlled trials and data from real‐life cohorts.